Analysis of Factors Affecting Commitment and Ability of Families to Early Detection in Stunting - Nursalam Nursalam; Sri Utami; Rekawati Susilaningrum (Jurnal Keperawatan Padjadjaran, 2021)
Background: Stunting is a public health problem in the world, stunting will have an impact on the growth and development of children. The first 1000 days of life are important to prevent stunting, this is a period when the child’s body system experiences physical growth, intelligence, and children’s abilities. Purpose:This study aims to analyze the factors that influence family commitment and ability to detect stunting. Methods: A cross-sectional study was conducted on 130 respondents in public health center, Surabaya, Indonesia. Data was collected through a questionnaire via Google form, anonymous online research questionnaire was collected through social media, such as Telegram, WhatsApp, Facebook which was conducted from June to September 2020. Data were analyzed using SPSS software version 21 with multivariate logistic regression. Results: The dominant factor affecting the commitment in early detection of stunting was community resources (p = 0.006; CI 95% = 0.888 - 4.272). Supporting (p = 0.000; CI 95% = 1.757-79.610), empowering (p = 0.000; CI 95% = 0.603 - 18.363) and enabling (p = 0.000; CI 95% = 0.395 - 4.869) were dominant factors that affected the ability to detect early stunting. Conclusion: The behavior of commitment and willingness in early detection of stunting in children is an important role that every parent must have with full support from the family. The main factor influencing family commitment is community resources and the main factor is the willingness of early detection to support, empower and enable families to provide care for their children.